1998
DOI: 10.1063/1.556024
|View full text |Cite
|
Sign up to set email alerts
|

Electron Interactions With C3F8

Abstract: To aid the many and diverse applications for which perfluoropropane (C 3 F 8 ) is suited, we critically evaluate and synthesize existing knowledge on electron scattering and electron energy-loss processes for the C 3 F 8 molecule, and provide recommendations for the most reliable data. We also draw attention to electron-interaction data that are not presently available, but are needed for modeling the behavior of C 3 F 8 in practical uses, especially plasma processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…A number of TICSs have been previously reported for C 2 F 6 and C 3 F 8 , and those suggested in several reviews [37][38][39][40][41][42] have been included in Figs. 1(a) and 2(a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of TICSs have been previously reported for C 2 F 6 and C 3 F 8 , and those suggested in several reviews [37][38][39][40][41][42] have been included in Figs. 1(a) and 2(a).…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, there have been several reports of measurements for CF 4 , C 2 F 6 , and C 3 F 8 using a variety of other experimental methods. Christophorou and co-workers [37][38][39][40] have summarized all measurements performed pre-2002, providing several sets recommended cross sections for comparison: Winters and Inokuti [70], Flaherty et al [71], and Baio et al [72] reported data for CF 4 , C 2 F 6 , and C 3 F 8 , respectively; Mi and Bonham [73] determined neutral dissociation cross sections for these three molecules at 22, 25, and 34 eV; and Montlagh and Moore [74] reported detailed neutral dissociation cross sections for CF 4 as well as preliminary data from measurements on C 2 F 6 and C 3 F 8 . In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the collision cross-section, the swarm parameters for each single gas as well as the values compared with the experimental breakdown voltage value and adjusted are used [22,23]. The analytical conditions are shown below.…”
Section: Results Of Boltzmann Equation Analysismentioning
confidence: 99%
“…In order to obtain the first term of equation (5), we use the EEDF's f (E/N, ε) from section 3.2 and reference data for the ionization cross section σ i for SF 6 [22] and C 3 F 8 [23]. The second term is calculated from the measured ν eff /N -and ν B eff /N -data (see section 3.1), which is fitted with smoothing spline to evaluate the fit in 1 Td steps.…”
Section: Obtaining the Right-hand Side G(e/n )mentioning
confidence: 99%